The gut microbiome: a vital link to hyperuricemia, gout and acute flares? - Wang, Wei; Wang, Liping; Chen, Jing; Yang, Xinyi; Guo, Qingyu; Zhang, Zhen; Liang, Jingjing; Gu, Ping; Shao, Jiaqing (Frontiers in Endocrinology, 2025)
ObjectivesTo explore the associations between the gut microbiome and asymptomatic hyperuricemia, as well as acute gout flares.MethodsForty-three Chinese participants were divided into healthy and hyperuricemic groups according to serum uric acid (SUA) levels. The hyperuricemia group were further separated into asymptomatic hyperuricemia (HUA) and gout patients on the basis of their clinical symptoms. In addition, the gout group was further divided into intercritical gout and acute gout groups on the basis of the claim of joint pain and relevant clinical parameters. 16S rRNA sequencing was used to evaluate the microbiome composition of all the groups.ResultsA dramatic decreasing trend in microbial richness and diversity was observed in hyperuricemic patients compared with healthy controls. The same decreasing trend in microbial relative abundance was also observed. The butyrate-producing genera Faecalibacterium, Coprococcus and Enterococcus were markedly decreased in hyperuricemic patients. Moreover, opportunistic pathogens, such as the phylum Proteobacteria and genus Fusobacterium, were enriched in the hyperuricemia group. Furthermore, the gut microbiota of gout patients also exhibited significantly reduced microbial diversity compared with asymptomatic hyperuricemic patients, characterized by decreased richness of the genera Dialister, Ruminococcus, and Faecalibacterium. Greater differences in microbial richness and diversity can still be observed when gout flares occur. The abundances of Bacteroides and Lachnospira genera decreased in the acute gout stage.ConclusionOur study revealed that community richness and diversity change during the process of gout or HUA, especially during acute gout flares. Metagenomic species were significantly altered during different stages of hyperuricemia.